If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2a + 12)(3a + 3) = a + 3 Reorder the terms: (12 + 2a)(3a + 3) = a + 3 Reorder the terms: (12 + 2a)(3 + 3a) = a + 3 Multiply (12 + 2a) * (3 + 3a) (12(3 + 3a) + 2a * (3 + 3a)) = a + 3 ((3 * 12 + 3a * 12) + 2a * (3 + 3a)) = a + 3 ((36 + 36a) + 2a * (3 + 3a)) = a + 3 (36 + 36a + (3 * 2a + 3a * 2a)) = a + 3 (36 + 36a + (6a + 6a2)) = a + 3 Combine like terms: 36a + 6a = 42a (36 + 42a + 6a2) = a + 3 Reorder the terms: 36 + 42a + 6a2 = 3 + a Solving 36 + 42a + 6a2 = 3 + a Solving for variable 'a'. Reorder the terms: 36 + -3 + 42a + -1a + 6a2 = 3 + a + -3 + -1a Combine like terms: 36 + -3 = 33 33 + 42a + -1a + 6a2 = 3 + a + -3 + -1a Combine like terms: 42a + -1a = 41a 33 + 41a + 6a2 = 3 + a + -3 + -1a Reorder the terms: 33 + 41a + 6a2 = 3 + -3 + a + -1a Combine like terms: 3 + -3 = 0 33 + 41a + 6a2 = 0 + a + -1a 33 + 41a + 6a2 = a + -1a Combine like terms: a + -1a = 0 33 + 41a + 6a2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. 5.5 + 6.833333333a + a2 = 0 Move the constant term to the right: Add '-5.5' to each side of the equation. 5.5 + 6.833333333a + -5.5 + a2 = 0 + -5.5 Reorder the terms: 5.5 + -5.5 + 6.833333333a + a2 = 0 + -5.5 Combine like terms: 5.5 + -5.5 = 0.0 0.0 + 6.833333333a + a2 = 0 + -5.5 6.833333333a + a2 = 0 + -5.5 Combine like terms: 0 + -5.5 = -5.5 6.833333333a + a2 = -5.5 The a term is 6.833333333a. Take half its coefficient (3.416666667). Square it (11.67361111) and add it to both sides. Add '11.67361111' to each side of the equation. 6.833333333a + 11.67361111 + a2 = -5.5 + 11.67361111 Reorder the terms: 11.67361111 + 6.833333333a + a2 = -5.5 + 11.67361111 Combine like terms: -5.5 + 11.67361111 = 6.17361111 11.67361111 + 6.833333333a + a2 = 6.17361111 Factor a perfect square on the left side: (a + 3.416666667)(a + 3.416666667) = 6.17361111 Calculate the square root of the right side: 2.484675252 Break this problem into two subproblems by setting (a + 3.416666667) equal to 2.484675252 and -2.484675252.Subproblem 1
a + 3.416666667 = 2.484675252 Simplifying a + 3.416666667 = 2.484675252 Reorder the terms: 3.416666667 + a = 2.484675252 Solving 3.416666667 + a = 2.484675252 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3.416666667' to each side of the equation. 3.416666667 + -3.416666667 + a = 2.484675252 + -3.416666667 Combine like terms: 3.416666667 + -3.416666667 = 0.000000000 0.000000000 + a = 2.484675252 + -3.416666667 a = 2.484675252 + -3.416666667 Combine like terms: 2.484675252 + -3.416666667 = -0.931991415 a = -0.931991415 Simplifying a = -0.931991415Subproblem 2
a + 3.416666667 = -2.484675252 Simplifying a + 3.416666667 = -2.484675252 Reorder the terms: 3.416666667 + a = -2.484675252 Solving 3.416666667 + a = -2.484675252 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3.416666667' to each side of the equation. 3.416666667 + -3.416666667 + a = -2.484675252 + -3.416666667 Combine like terms: 3.416666667 + -3.416666667 = 0.000000000 0.000000000 + a = -2.484675252 + -3.416666667 a = -2.484675252 + -3.416666667 Combine like terms: -2.484675252 + -3.416666667 = -5.901341919 a = -5.901341919 Simplifying a = -5.901341919Solution
The solution to the problem is based on the solutions from the subproblems. a = {-0.931991415, -5.901341919}
| 4(x-10)=6(2-x)-6 | | -2+z+y+2=6 | | x^2/3-x/2=9 | | log[5](x^2-3x)=log[5](2x+6) | | x^4-17x^2+18=0 | | 0.4x^2-2.4x=0 | | 5x-12=x+6 | | x^2+9+8x=0 | | 6x^2-38X-14=-26 | | -1-5h=10 | | 2x-18=-38+7x | | 7z-14=-35+4z | | 39-15x=-31-5X | | i+16=4 | | 3x+14=-22-6x | | (-2+z)+(-7+(-3z))+2=6 | | 6c+4d=48 | | -4/-3=x | | 3=h+13 | | x/2=34 | | a+10=-8 | | 57-3x=8-10x | | 7d^2+10(1-6d^2)-4d= | | x+(x-6)*0.2=12 | | 11y+48=3y | | 13/14z-12/13=11/13 | | b/5-3=-4 | | 5x+6=-34-5x | | x*.0925=10 | | log(3+1)=2 | | lg(3+1)=2 | | 25x^2-50x+2=0 |